2002
DOI: 10.1007/s00210-002-0562-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stability of wild-type and constitutively active α 2A -adrenoceptors by ligands with agonist, silent and inverse agonist properties

Abstract: The hypothesis that prolonged treatment of a constitutively active receptor with inverse agonists may lead to increased receptor density was tested for the alpha(2)-adrenoceptor (AR) inverse agonist (+)-RX 811059 at both the wild-type (WT) and Thr(373)Lys alpha(2A) ARs in CHO-K1 cells by monitoring [(3)H]RX 821002 and [(35)S]GTPgammaS binding responses. One-hundred micromolar KCl instead of NaCl in the [(35)S]GTPgammaS membrane binding assay favoured the detection of a high-magnitude constitutive alpha(2A) AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…The N514Y M 3 (but not the WT-M 3 ) receptor expression level could be significantly increased by chronic (24 h) incubation in the presence of an inverse agonist. Ligand-mediated receptor up-regulation has been reported previously for constitutively active mutant receptors (Smit et al, 1996;Stevens et al, 2000;Li et al, 2001;Pauwels and Tardif, 2002), although the precise molecular mechanisms involved are still debated (Parnot et al, 2002). For some CAM-GPCR, the degree of up-regulation is positively correlated with both the degree of constitutive activity in the system and the ability of a ligand to decrease basal activity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The N514Y M 3 (but not the WT-M 3 ) receptor expression level could be significantly increased by chronic (24 h) incubation in the presence of an inverse agonist. Ligand-mediated receptor up-regulation has been reported previously for constitutively active mutant receptors (Smit et al, 1996;Stevens et al, 2000;Li et al, 2001;Pauwels and Tardif, 2002), although the precise molecular mechanisms involved are still debated (Parnot et al, 2002). For some CAM-GPCR, the degree of up-regulation is positively correlated with both the degree of constitutive activity in the system and the ability of a ligand to decrease basal activity.…”
Section: Discussionmentioning
confidence: 92%
“…If a CAM-GPCR functions in a similar way to its cognate agonist-induced WT counterpart, it would follow that only inverse agonists would cause up-regulation by virtue of stabilizing the inactive conformation (Parnot et al, 2002). However, other studies (Gether et al, 1997;Pauwels and Tardif, 2002) have shown that the creation of a CAM can diminish stabilizing constraints within the receptor, leading to an inherently unstable receptor that is more susceptible to destabilization and/or proteolytic degradation (Stevens et al, 2000). In this case, the expression level of the mutant is increased by any ligand [(inverse) agonist/antagonist] regardless of its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…‫,ءء‬ p Ͻ 0.01; ‫,ء‬ p Ͻ 0.05. under our conditions because our treatment with inverse agonists was relatively short. The increased cell surface expression could be due to the stabilization of the receptor, either intracellularly to increase receptor maturation and expression (Petaja-Repo et al, 2002) or by stabilizing the receptor on the cell surface (Wilson and Limbird, 2000;Pauwels and Tardif, 2002). Because there is no indication that the antagonists we used in our experiments are cell-permeable, we would favor the hypothesis that the inverse agonists possibly stabilize constitutively active receptor on the cell surface and possibly interfere with the constitutive internalization process.…”
Section: Inverse Agonists Of the Cyslt 1 Receptor 105mentioning
confidence: 96%
“…Some structurally labile receptors could be stabilized by expression in the presence of ligands (Gether et al 1997;Pauwels and Tardif 2002;Roth et al 2008). Also, the agonist HA and the inverse agonist THIO were able to increase the B max value of [ 3 H]HA binding to wild-type hH 4 R ).…”
Section: Structural Instability Of the H Ce2 H 4 Rmentioning
confidence: 95%